The Routledge companion to motherhood
1 online resource
Keywords: "Interdisciplinary and intersectional in emphasis, the Routledge Companion to Motherhood brings together essays on current intellectual themes, issues, and debates, while also creating a foundation for future scholarship and study as the field of Motherhood Studies continues to develop globally. This Routledge Companion is the first extensive collection on the wide-ranging topics, themes, issues, and debates that ground the intellectual work being done on motherhood. Global in scope and including a range of disciplinary perspectives, including anthropology, literature, communication studies, sociology, women's and gender studies, history, and economics, this volume introduces the foundational topics and ideas in motherhood, delineates the diversity and complexity of mothering, and also stimulates dialogue among scholars and students approaching from divergent backgrounds and intellectual perspectives. This will become a foundational text for academics in Women's and Gender Studies and interdisciplinary researchers interested in this important, complex and rapidly growing topic. Scholars of psychology, sociology or public policy, and activists in both university and workplace settings interested in motherhood and mothering will find it an invaluable guide"--